(untitled) (Wudil Journal of Science and Technology Education, 2025)
Water is universally recognized as the foundation of life, playing roles that go far beyond hydration. It acts as a solvent, transport medium, temperature regulator, and the carrier of electrolytes that sustain nearly all biological processes. Electrolytes such as sodium, potassium, calcium, magnesium, chloride, bicarbonate, and phosphate are critical for nerve transmission, muscle contraction, acid-base regulation, and cellular homeostasis. This paper explores the essential role of water as an electrolyte solvent to life, emphasizing its physiological importance, storage in the body, interaction with electrolytes, balance across compartments, and the dietary sources that naturally replenish electrolytes. By taking a health-oriented approach, the paper underscores how everyday hydration and nutrition practices can maintain optimal electrolyte balance and prevent common health challenges such as dehydration, fatigue, and muscle dysfunction. Therefore, it was recommended that specific actions be taken to promote hydration and electrolyte health across all sectors, including individual, clinical, and policy domains.